Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (